Educational strategies in realistic simulation: developing competencies and skills in emergencies and emergencies (Research, Society and Development, 2020)
This study aims to share an experience report on the realization of realistic simulation educational strategies in an Urgency and Emergency discipline. This report belongs to the discipline of Urgencies and Emergencies held during the period from July to December 2019, with a workload of 60 hours / class and 17 students enrolled. Data collection was performed through the teacher's field diary and presented in this study through approximations with the Bardin Content Analysis (2016). The results and discussions followed the presentation threshold of the discipline construction, intuiting about its objectives, skills and competencies. Also articulating the construction of educational strategies applied in the discipline with the use of realistic simulation and emphasizing the space of the evaluation process in this field. Thus, it is clear that realistic simulation enables countless ways to compose educational strategies in the disciplinary set of urgencies and emergencies, prompting the formation of the skills and competencies needed for the student.